Submit a question to our community and get an answer from real people.

Solve for z. -6z+2=3z+4z+28

how would you solve this equation

Report as

-6z+2=3z+4z+28

combine like terms using distributive property a(b + c) = ab + ac
-6z+2=7z+28

addition property of equality: if a = b then a + c = b + c
2 = 13z + 28

subtraction property of equality: if a = b then a - c = b - c
subtract 28 from each side
-26 = 13z

division property of equality: if a = b then a / c = b / c (c not equal to zero)
divide each side by 13
z = -2

get free math homework help at http://www.mathskey.com/cms/index.php?option=com_fireboard&Itemid=45

Report as

You can solve this equation by collecting the like terms together. This can be done by working it out to be -6z-3z-4z=28-2. After collecting the like terms together as done, start subtracting and adding on the number. After the subtraction and addition, the result will be -13z=26. Since you're finding y, the answer could be either z=26/-13 or z=-26/13.

Report as

z = -2